217k views
0 votes
Simplify the expression and rationalize the demonimator when appropriate, please show steps : >

Simplify the expression and rationalize the demonimator when appropriate, please show-example-1
User Jonno
by
5.4k points

2 Answers

5 votes

Answer:

-3v²t

Explanation:


\sqrt[3]{3t^4v^2}  \sqrt[3]{-9t^-1v^4}

=
\sqrt[3]{3t} \sqrt[3]{v^2t} \sqrt[3]{-9v^4t^-1}

=
\sqrt[3]{3t} (-\sqrt[3]{9v^4/t)} \sqrt[3]{v^2t}

= -
\sqrt[3]{3t}  \sqrt[3]{v^2 9v^4/t}t

= -
\sqrt[3]{3}  \sqrt[3]{9t}  \sqrt[3]{v^6}

= -
\sqrt[3]{3*9}v^2t

= -
\sqrt[3]{27} v^2t

= -3v²t

User Virgil
by
5.7k points
2 votes

Answer:


=-3tv^2

Explanation:

So we have the expression:


\sqrt[3]{3t^4v^2}\sqrt[3]{-9t^(-1)v^4}

To simplify, combine the two radicals. Since they have the same index, we can combine them. Thus:


=\sqrt[3]{(3t^4v^2)(-9t^(-1)v^4)}

Combine like terms:


=\sqrt[3]{(3\cdot -9)(t^4\cdot t^(-1))(v^2\cdot v^4)}

Multiply. When multiplying the exponents, simply add the exponents:


=\sqrt[3]{-27t^3v^6}

Now, simplify. Note that -27 can be written as (-3)^3. t^3 can be written as (t)^3 and v^6 can be written as (v^2)^3. Thus:


=\sqrt[3]{(-3)^3(t)^3(z^2)^3}

Combine them all under one exponent:


=\sqrt[3]{(-3tv^2)^3}

Cancel out the cube root:


=-3tv^2

And this is the simplest it can get.

And we are done :)

Edit: Typo

User Igon
by
5.5k points